Prevalence and molecular characterization of Salmonella serovars in milk and cheese in Mansoura city, Egypt - El-Baz, Amira Hussein; El-Sherbini, Mohammed; Abdelkhalek, Adel; Al-Ashmawy, Maha Abdou (Journal of Advanced Veterinary and Animal Research, 2017)
Objective: This study was conducted to determine the prevalence of Salmonella in milk (farm bulk milk, raw market milk) and cheese (kareish, white soft cheese) samples that were collected randomly from farms, supermarkets, small vendors and shops in different districts of Mansoura city, Egypt. Materials and methods: A total of 100 farm bulk milk, raw market milk, kareish cheese and white soft cheese samples (25 of each) were screened for the prevalence of Salmonella spp. The Salmonella isolates were isolated and identified by conventional bacteriological techniques, which were further confirmed genetically by polymerase chain reaction (PCR) based on the presence of invA gene. Finally, the isolates were serotyped. Results: Salmonella could be detected in 15%(n=15/100) samples with a prevalence of 12%(n=3/25), 24%(n=6/25), 20%(n=5/25) and 4%(n=1/25) in raw market milk, raw farm bulk milk, kareish cheese and white soft cheese, respectively. The Salmonella isolates were serotyped into S. enteritidis 33.3%(n=9/27) which was the most frequent, followed by S. typhimurium 25.9%(n=7/27), S. heidelberg 14.8%(n=4/27), S. infantis 11.11%(n=3/27), S. tsevie 11.11%(n=3/27) and S. haifa 3.7%(n=1/27). Conclusion: The present study confirms the presence of Salmonella in milk and cheese samples in Mansoura, Egypt, indicating that the dairy products can act as potential sources of Salmonella infection. Thus, appropriate hygienic measures are suggestive for combating Salmonellosis in Egypt. http://doi.org/10.5455/javar.2017.d189